ANGKA KETAHANAN HIDUP 3 TAHUN PASIEN KARSINOMA NASOFARINGS YANG MENDAPAT CONCURRENT CHEMORADIOTHERAPY DI BAGIAN TELINGA HIDUNG TENGGOROK RSUP DR. SARDJITO PADA TAHUN 2008-2010 - , MERI ESTIVO SIHOMBING; , dr. Sagung Rai Indrasari, M.Kes., Sp. THT-KL (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Nasopharyngeal carcinoma (NPC) is an epithelial malignancy on posterior nasal cavity. NPC is the most common malignancy in Ear Nose Throat â Head Neck Department of RSUP. Dr. Sardjito. On its early stage, NPC can be treated with radiotherapy alone. But on the more advance stage, chemotherapy is needed. Previous studies show that concurrent chemoradiotherapy (CCRT) gives better patientâs survival rate. Determining survival rate is something thatâs have to be done because it can be a determinant of diseaseâs prognostic. Objective: To determine the 3-years survival rate of patients with NPC that acquired concurrent chemoradiotherapy in Ear Nose Throat Department of RSUP Dr. Sardjito in 2008-2010. Method: A descriptive-analytical study using Kaplan- Meier survival analysis to determine the 3-years survival rate of NPC patients who undergo CCRT. Samples are obtained from January 2008 to December 2010, where 20 NPC patients met the inclusion and exclusion criteria. Result: The 3-years survival rate of NPC patients who acquired concurrent chemoradiotherapy in Ear Nose Throat Department of RSUP. Dr. Sardjito in 2008-2010 is 50% with mean survival time of 22,8 months altogether.